"We are talking about practice": the Influence of mindfulness vs. relaxation training on athletes` attention and well-being over high-demand intervals - Rooks, J. D.; Morrison, A. B. (Journal of Cognitive Enhancement, 2017)
We investigated the impact of short-form mindfulness training (MT) vs. relaxation training (RT) programs on sustained attention and emotional well-being in college football players (N = 100) during their high-demand pre-season training interval. Participants received 4 weeks of MT (n = 56) or RT (n = 44) and completed the Sustained Attention to Response Task (SART) and questionnaires assessing emotional well-being before and after the training period. Sustained attention was assessed via SART outcomes indexing performance (A'), reaction time variability (intraindividual coefficient of variation (ICV)), and self-reported mind wandering and meta-awareness (Probe 1, Probe 2), while emotional well-being was assessed via the Positive and Negative Affect Schedule (PANAS), the State-Trait Anxiety Inventory (State; STAI-S), and the Center for Epidemiological Studies Depression (CES-D) scale. Overall, behavioral measures of sustained attention (A', ICV) and self-report measures of emotional well-being (PANAS Positive, STAI-S, CES-D) declined during the training interval, suggesting that this was a high-demand interval with cognitive and emotional consequences. Further, while group effects comparing training programs were non-significant, greater engagement (i.e., practice and adherence) in MT, but not RT, predicted greater benefits, akin to protection-from-decline, on SART behavioral indices (A', ICV). Greater engagement in both MT and RT predicted negative change in anxiety and positive change in positive affect over the high-demand interval. These results suggest that, similar to physical training, athletes must sufficiently engage in MT and RT to experience the distinct and overlapping benefits these programs offer over cognitively and emotionally demanding intervals, such as pre-season athletic training.